An exploratory study into the effects of extraordinary nature on emotions, mood, and prosociality - Joye, Yannick; Bolderdijk, Jan Willem (Frontiers in Psychology, 2015)
Environmental psychology research has demonstrated that exposure to mundane natural environments can be psychologically beneficial, and can, for instance, improve individuals' mood and concentration. However, little research has yet examined the psychological benefits of extraordinary, awe-evoking kinds of nature, such as spectacular mountain scenes or impressive waterfalls. In this study, we aimed to address the underrepresentation of such extraordinary nature in research on human—nature interactions. Specifically, we examined whether watching a picture slideshow of awesome as opposed to mundane nature differentially affected individuals' emotions, mood, social value orientation (SVO), and their willingness to donate something to others. Our analyses revealed that, compared to mundane nature and a neutral condition, watching awesome natural scenes and phenomena had some unique and pronounced emotional effects (e.g., feeling small and humble), triggered the most mood improvement, and led to a more prosocial SVO. We found that participants' willingness to donate did not differ significantly for any of the conditions.